Fence. Volume one - Pacat, C. S. (BOOM! Box, 2018)
Nicholas, the illegitimate son of a retired fencing champion, dreams of getting the chance and training to actually compete in fencing. After getting a scholarship to the prestigious Kings Row private school, Nicholas finds himself in the cut-throat world of fencing, facing his golden-boy half brother and the unbeatable Seiji Katayama.